Witkacy, Cocteau i inni. Amatorskie filmy Augusta Zamoyskiego - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
The article analyses the contents of a collection of more than one hundred amateur films made by the famed Polish sculptor August Zamoyski. This unique collection of 9.5 mm films of great archival value was recently transferred to Poland and is now held by the National Audiovisual Institute.